Energy policies for sustainable development in South Africa's residential and electricity sectors - Winkler, Harald (University of Cape Town, 2014)
Includes bibliographical references. === Harald Winkler's thesis examines "Energy policies for sustainable development in South Africa's residential and electricity sectors: Implications for mitigating climate change". The research question asks whether there are energy policies that will make South Africa's energy development more sustainable economically, socially and environmentally, especially in the context of the local environment. Energy policies for sustainable development are explored as an approach to mitigating climate change. A methodology combining three major components is developed - modelling, evaluation of indicators of sustainable development and policy analysis. The analysis explicitly starts from development objectives. 'Backcasting' from development objectives has been not been implemented in national energy models in developing countries. Within the modeling component, the residential sector is disaggregated into six household types for the first time in a national energy model for South Africa. Energy policies for sustainable development in two sectors are identified to meet the c0untry's development objectives. Making residential energy more sustainable includes cleaner and more efficient ways of providing energy services - lighting, water heating, cooking and heating. The thesis also analyses four major electricity supply options - renewable energy, nuclear, importing hydro or natural gas. The thesis develops an analytical approach that for considering energy policies that incorporates environmental concerns. Identified policies are quantified in an energy-economic modeling framework. A wide variety of data sources is used, drawing on statistical information, official energy data, utility statistics, journal articles and research reports. Indicators of sustainable development provide a framework for assessing the suitability of suggested policy cases, while policy analysis considers their implementation for both energy and climate policies. A contribution of the thesis lies in combining these analytical tools to identify energy policies that promote both local sustainable development and mitigate climate change. The thesis finds solar water heating and efficient housing rank higher than alternatives in all dimensions of sustainable development for the residential sector. These policies provide cleaner energy services, reduce fuel use and yield cost savings for households. The latter is significant in reducing the electricity burden, particularly for poorer households. A more equitable distribution of energy services favours social sustainability and reduces inequalities. Emissions in the order of 1- 10 Mt CO₂-equiv/year can be avoided. The investment requirement is relatively modest. However, the residential sector will not deliver the largest absolute energy savings and associated emission reductions.